Governmental power and human rights in times of emergency: a brief survey on Article 150 of Malaysian Constitution / Abdul Khalid Shah Mohamad Omar - Mohamad Omar, Abdul Khalid Shah (Faculty of Law, 1986)
This project is written especially for the academic requirement by the School of Administration and Law for the completion of my final year study as a law student. My favourite subject is Constitutional Law and 1 therefore choose this topic as my project paper: Govermental power And Human Rights In 'r i me s Of Emergency - a brief survey on Article 150 of Malaysian Constitution. This project paper is a study concerning the power confer by Article 150 to the Yang DiPertuan Agong who represent the government in exce r-ci s i ng such power in times of emergency and the restriction thereof. This proj ect will also touch upon the 'Fundamental Rights I Incorporated in the Malaysia Consti tution and the effect of emergency powers to such rights. Most of the discussion is focus in Chapter One and Two. Chapter One gives an introduction about the Federal Constitution of Malaysia which is discuss in three parts: (1) Its brief history (2) Provision of Fundamental Rights and (3) Provision of Article 150. Chapter Two deals with Article 150 in detail and is divided into two parts: (1) Proclaimation of Emer gency and (2) Emergency Legislation. I hope this project paper will be useful as reference to all future law student in Constitutional Law.